THE IMPACT OF SOCIAL MEDIA ON YOUTH MENTAL HEALTH (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
Abstract        Social media has become an integral part of young people’s daily lives offering unprecedented opportunities for communication education and creativity however excessive and uncontrolled use has raised concerns about its negative impact on psychological well-being This article explores both the positive and negative effects of social media on youth mental health focusing on issues such as anxiety depression cyberbullying and identity formation The discussion emphasizes the importance of digital literacy parental involvement and policy regulations as effective strategies to reduce risks and promote balanced use The findings suggest that social media can be a beneficial tool when used responsibly but may cause serious mental health problems if misused